No expatriate is an island: the role of salient stakeholders’ support in international assignments - Chan, Hak Liong; Dahlia Zawawi; Siew, Imm Ng; Debbra Toria Nipo (Emerald Group Publishing Ltd., 2021)
Purpose – International assignments are an effective tool to develop employees’ cultural competencies, yet expatriate failure rates remain high. This paper aims to examine salient stakeholders’ (i.e. organisations, host country nationals (HCNs) and spouses) support as antecedents of expatriates’ work adjustment and task performance. It also explores work adjustment as a mediator between support and task performance. Design/methodology/approach – Adopting the quantitative approach, survey data were collected from 112 expatriates who were married and based in organisations in Malaysia. Partial least squares-structural equation modelling was employed to analyse the data. Findings – The findings validate the direct influences of perceived organisational support (POS) on work adjustment, HCN support on work adjustment, and spousal support on task performance. The indirect effect of HCN support on task performance through work adjustment was also established. When expatriates’ work adjustment improves as a result of receiving HCN support, their task performance is enhanced. Practical implications – This study evidences that expatriate-hiring firms should provide suitable support for expatriates when they work overseas. Local employees and spouses should likewise be tasked to help expatriates maximise their full potential in achieving successful performance in their assignments. Originality/value – The contribution of this study is the exploration of the relationships between support, work adjustment and task performance among expatriates. It also adds to the limited knowledge on the role of specific stakeholders in the expatriate context.